1995
DOI: 10.1111/j.1530-0277.1995.tb00992.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain Proton Magnetic Resonance Spectroscopy Studies in Recently Abstinent Alcoholics*

Abstract: Chronic alcohol-dependent patients have reduced brain volumes and concomitant neurobehavioral deficits that may recover during abstinence. In 10 chronic alcoholic patients, using localized proton magnetic resonance spectroscopy, we found reliable increases during the first 3-4 weeks of abstinence in the concentrations within the superior cerebellar vermis of choline (Cho)-containing compounds relative to the neuronal marker, N-acetylaspartate (NAA). Lesser changes were observed following 1 month of abstinence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
2
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(51 citation statements)
references
References 45 publications
3
45
2
1
Order By: Relevance
“…In alcoholism uncomplicated by WE, MRS provides evidence for abnormally low peaks of N-acetylaspartate (NAA), a marker for mature viable neurons, or choline (Cho), an index of membrane turnover, in frontal, parietal, or cerebellar regions within a month of withdrawal (Durazzo et al, 2004;Fein et al, 1994;Jagannathan et al, 1996;Schweinsburg et al, 2003Schweinsburg et al, , 2001Seitz et al, 1999) followed by improvement in NAA or Cho, suggesting neuronal recovery (Bendszus et al, 2001;Ende et al, 2005;Martin et al, 1995;Parks et al, 2002). In WE, whether preceded by alcoholism or other precipitating condition, an early deficit in NAA can improve, more so in the thalamus than cerebellum (Murata et al, 2001), a recovery pattern noted earlier by Victor et al (1971Victor et al ( , 1989.…”
Section: Introductionmentioning
confidence: 99%
“…In alcoholism uncomplicated by WE, MRS provides evidence for abnormally low peaks of N-acetylaspartate (NAA), a marker for mature viable neurons, or choline (Cho), an index of membrane turnover, in frontal, parietal, or cerebellar regions within a month of withdrawal (Durazzo et al, 2004;Fein et al, 1994;Jagannathan et al, 1996;Schweinsburg et al, 2003Schweinsburg et al, , 2001Seitz et al, 1999) followed by improvement in NAA or Cho, suggesting neuronal recovery (Bendszus et al, 2001;Ende et al, 2005;Martin et al, 1995;Parks et al, 2002). In WE, whether preceded by alcoholism or other precipitating condition, an early deficit in NAA can improve, more so in the thalamus than cerebellum (Murata et al, 2001), a recovery pattern noted earlier by Victor et al (1971Victor et al ( , 1989.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the longitudinal NAA increases observed in nsALC suggest greater recovery of neuronal structural elements or metabolism, while Cho increases may indicate normalization of parenchymal cell membrane synthesis/turnover or recovery of para-hippocampal cortex and myelin (Harding et al, 1997;Martin et al, 1995). Previous studies in abstinent alcoholics did not evaluate smoking effects, although the samples presumably included a significant number of smokers; these studies generally demonstrated little or no NAA recovery in major lobes and cerebellum over the first month of abstinence Parks et al, 2002), but see (Bendszus et al, 2001).…”
Section: Mtl Metabolite Concentrationsmentioning
confidence: 99%
“…MRI volumetric studies, however, cannot distinguish between injury to neuronal or glial cells, and they are not sensitive to tissue density changes reported in recovering alcoholics (Trabert et al, 1995). Proton magnetic resonance spectroscopy ( 1 H MRS) may distinguish between neuronal and glial injury and may be sensitive to changes in brain tissue density (Martin et al, 1995). We used 1 H-MRS at short echo time to measure four major metabolites (Ross and Bluml, 2001): N-acetyl-aspartate (NAA), an accepted marker of neuronal viability, is observed only in mature neurons and their processes; decreased NAA may reflect neuronal loss, atrophied dendrites and axons, and/or derangements of neurometabolism; cholinecontaining compounds (Cho) are believed to be involved in cell membrane breakdown and synthesis; creatine-containing metabolites (Cr) consist of creatine and phosphocreatine, which are involved in cell bioenergetics, and myo-inositol (m-Ino) is a putative marker of astrocytes and may also function as an osmolyte (Schweinsburg et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the alcoholics in the present study were abstinent from alcohol for at least several months. As normalization of metabolite levels can occur with extended sobriety (Mann et al, 2001;Martin et al, 1995;Seitz et al, 1999;but see, O'Neill et al, 2001a), the metabolite values of the alcoholic group in the present study may reflect recovery. The volumetric MRS imaging (MRSI) approach permitted the measurement of neocortical regions not achievable with the large single-voxel approach.…”
Section: Discussionmentioning
confidence: 82%